2019
DOI: 10.1093/tbm/ibz186
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators of peer coaching/support engagement and dissemination among women at risk for and surviving with breast cancer

Abstract: One-on-one peer coaching/support programs hold promise in promoting healthy outcomes among women at risk for and surviving with breast cancer, with the potential to bridge gaps in “whole person care.” Although popularly cited for their benefits, emerging evidence is mixed and suggests that peer support program impacts may be attenuated by individual- and community-specific factors. We evaluated a national not-for-profit breast cancer organization’s peer support program outcomes (2015–2018) serving women from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…These findings regarding the role of peer support in navigating women to services are consistent with prior research on cancer control and accessing care, as well as women's overall satisfaction with the services they receive. 17,19 This may occur in the context of both QoL and SDoH, whose significant influences in survivors' lives cannot be ignored. We observed that these relationships can be attenuated by differences in QoL and SDoH as would be expected based on the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings regarding the role of peer support in navigating women to services are consistent with prior research on cancer control and accessing care, as well as women's overall satisfaction with the services they receive. 17,19 This may occur in the context of both QoL and SDoH, whose significant influences in survivors' lives cannot be ignored. We observed that these relationships can be attenuated by differences in QoL and SDoH as would be expected based on the literature.…”
Section: Discussionmentioning
confidence: 99%
“…These navigators were trained to share their firsthand experiences with other women in similar situations-acting as peer supporters. In a study by Rehberg et al, 19 most women who used peer support for breast cancer-related services had connected with a CBO online or were referred by a family member or friend. Referral to peer support by a trusted source was more likely to result in a favorable outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Peer coaching and navigation also emerged as a key solution where AYAs could be trained to guide one another through the difficulties faced. Some organizations do offer this type of peer-driven support but not all are specific to the AYA population [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, peer support given by individuals who have experienced similar processes can lead to sustaining effective communication with patients with cancer and presenting a new perspective on cancer experiences. In this process, both the physical activity levels and self‐esteem of the patients will be strengthened (Loprinzi Brauer et al, 2016; Rehberg et al, 2021; Walshe et al, 2020).…”
Section: Introductionmentioning
confidence: 99%